Análisis del mercado de derivados forwars para maquinaria pesada importada en el sector petrolero (periodo 2007-2017) (2019)
The present degree project explains the methodology and results to analyze the impact that the Forward Derivatives Market for heavy machinery imported for the oil sector (2007-2017), where a review of the modern portfolio theory is made, which is the basis for this type of derivatives market and hedging instruments in relation to underlying assets such as imported heavy machinery. Then, the heavy machinery imported together with its characteristics is identified, then variables and regulations of the forward derivative market are identified with the heavy machinery imported into the oil sector, which are diversification, systematic and non-systematic risk, market variables, risk-return ratio.